Discrete Cosine Transform and Singular Value Decomposition Based on Canny Edge Detection for Image Watermarking - Astuti, Erna Zuni; Sari, Christy Atika; Rachmawanto, Eko Hari; Astuti, Yani Parti; Oktaridha, Harwinanda; Isinkaye, Folasade Olubusola (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2023)
The development of an increasingly sophisticated internet allows for the distribution of digital images that can be done easily. However, with the development of increasingly sophisticated internet networks, it becomes an opportunity for some irresponsible people to misuse digital images, such as taking copyrights, modification and duplicating digital images. Watermarking is an information embedding technique to show ownership descriptions that can be conveyed into text, video, audio, and digital images. There are 2 groups of watermarking based on their working domain, namely the spatial domain and the transformation domain. In this study, three domain transformation techniques were used, namely Singular Value Descomposition (SVD), Discrete Cosine Transform (DCT) and Canny Edge Detection Techniques. The proposed attacks are rotation, gaussian blurness, salt and pepper, histogram equalization, and cropping. The results of the experiment after inserting the watermark image were measured by the Peak Signal to Noise Ratio (PSNR). The results of the image robustness test were measured by the Correlation Coefficient (Corr) and Normalized Correlation (NC). The analysis and experimental results show that the results of image extraction are good with PSNR values from watermarked images above 50dB and Corr values reaching 0.95. The NC value obtained is also high, reaching 0.98. Some of the extracted images are of fairly good quality and are similar with the original image.